ANALISIS PENGARUH VARIABEL MAKROEKONOMI TERHADAP INFLASI DI INDONESIA SEBELUM DAN SESUDAH DITERAPKANNYA KEBIJAKAN INFLATION TARGETING FRAMEWORK PERIODE 2002:1 –2010:12 - Murti Sari Dewi (Media Ekonomi, 2011)
This thesis want to see effect of macroeconomics variables of inflation in Indonesia before and after Inflation Targeting Framework Policy period 2002:1 – 2010:12. The data used in this study is a secondary data obtained from Bank Indonesia. Variables are in use, among others: the level of inflation (CPI), the money supply, government expenditure, exchange rates against the U.S. dollar, and the dummy variable. Analysis tool used is a dynamic model. This model explains the influence of the relationship between the dependent variable with independent variables in the short and long term. The results of this study concluded that the variables in the money supply, government expenditure , and exchange rates have a significant effect on inflation in the long run, while in the short term had no significant effect on inflation, so that this study produces a long-term equation. Based on the results of previous studies both concluded that the variables in the money supply, government expenditure , and exchange rates have a significant effect on inflation in the long run, while in the short term had no significant effect on inflation.